INTERACTIVE VIDEO AS ENGLISH TEACHING MATERIALS FOR SPEAKING - Pramerta, I Gde Putu Agus (Fakultas Keguruan dan Ilmu Pendidikan (FKIP) Universitas Mahasaraswati Denpasar, 2018)
The process of learning English in SMP N 2 Penebel class VII C showed that students experienced obstacles in speaking. It could be seen from result of observation, interview and pre-test. It was 2.70 which is categorized below the passing grade minimum criteria: 3.0. Researcher indicated that it was because they seemed to be having lack of motivation in the English learning process. The use of interactive video in learning is necessary in order to improve students' motivation in speaking. Action research design was accommodated to help their problems. The researcher offered three kinds of tests. The result of pre-test was 2.70. After pre-test, the researcher went into cycle 1 which succeeded in improving their speaking from 2.70 to 2.96. In cycle 2, there was improvement up to 3.31. The use of interactive video gave positive responses to the students. As the result, their speaking could be improved.